THE EFFECT OF SOCIAL MEDIA MARKETING ACTIVITY, PROMOTION, PRICE AND CONSUMER ATTITUDE ON PURCHASING DECISION: BRAND IMAGE AS A MEDIATION VARIABLE - Khoirina, Najwa; Badriyah, Nurul; Mauladi, Kemal Farouq (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
In line with progress, the corporate world’s development is also expanding and progressing quickly in the economic sphere. Everybody is attempting to provide goods and services to satisfy the growing demands and preferences of customers. However, achieving this is not easy, because nowadays competition between companies has reached a very competitive stage. Research is to ascertain how social media marketing, or marketing through social media, affects consumer attitudes, prices, and promotions at PT. Indofood Sukses Makmur Tbk. These factors are mediated by brand image. With 116 respondents in the sample, this kind of research is quantitative, and SEM with the Smart PLS version 3.2.9 tool is the methodology employed. The tests that are employed include the hypothesis test, mediation test, inner model, and outer model. Based on the findings of the validity test, loading factor values greater than 0.7 and AVE values greater than 0.5 are regarded as valid. Cronbach Alpha and Composite Reliability ratings larger than 0.7 are indicators of reliability. in the reliability test. It is possible to draw the conclusion that social media marketing activity, promotion, price, and customer attitude all have a significant favorable impact (X1), (X2), (X3), and (X4) on purchasing decisions (Y). Direct-only nonmediation, as defined by the mediation test, includes price (X3), promotion (X2), social media marketing activity (X1), and purchasing decisions (Y) influenced by brand image (Z).